Contribuição do sistema colinérgico e da sinalização do NRF2/HO-1 para a ação anti-amnésica do 7-flúor-1,3- difenilisoquinolina-1-amina em camundongos - Müller, Sabrina Grendene (2019)
Dementia is a heterogenic condition characterized by different symptoms and theories about its pathogenesis, which results in difficult to understand and in the treatment of this disease. The 7-fluoro-1,3-diphenylisoquinoline-1-amine (FDPI) have been studied due to its multitarget properties, highlighting the modulation of GABAérgic and glutamatergic systems, antioxidant and anti-inflammatory. The Nuclear factor erythroid 2-related factor 2 (Nrf2), an important tool for cellular protection, regulates the transcription of antioxidant and cytoprotective genes. On the other hand, cholinergic system is responsible for modulation of important physiologic process, such as: stress response, attention, learning and memory. Thereby, the purpose of this study was to investigate the contribution of the cholinergic system and Nrf2/ Heme oxygenase (HO-1) signaling to the potential effect of FDPI on scopolamine-induced amnesia in mice (6835140116). Adult male Swiss mice received FDPI for 5 days (5, 10 e 25 mg/kg, i.g.), from day 3 to 5 the animals received scopolamine (1mg/kg, i.p.). The results demonstrated that the FDPI administration (10 and 25 mg/kg, i.g.) was effective to reverse the scopolamine-induced amnesia in the object recognition tests. The FDPI anti-amnesic effects seem to be related to the cholinergic system through the reestablishment of AChE levels and activity increased by scopolamine in the prefrontal cortex and hippocampus of mice. In addition, FDPI restored the M1 receptor levels decreased by scopolamine in both prefrontal cortex and hippocampus of mice. Scopolamine altered oxidative stress parameters differently in the prefrontal cortex and hippocampus of mice. Whereas the prefrontal cortex was susceptible to oxidative stress, none of the parameters evaluated was altered in the hippocampus. FDPI was effective in reversing scopolamine-enhanced oxidative stress parameters as well as the alterations in Nrf2/HO-1 signaling in the prefrontal cortex of mice. Taken together, the correlation results demonstrate the contribution of the cholinergic system, oxidative stress and Nrf2/HO-1 signaling to the effect of the FDPI in the object recognition tests.